British sign language - Deuchar, Margaret (London ; Boston : Routledge & Kegan Paul, 1984)
Lit.opg. ; reg.
Includes index.
Bibliography: p. [214]-226.
Keywords: British Sign Language; Deaf -- Education -- English language -- Great Britain